2014
DOI: 10.4103/2277-9175.129693
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of fixed daily 20 mg of isotretinoin in moderate to severe scar prone acne

Abstract: Background:Despite advances in acne therapy in recent years, treatment failure is common. Isotretinoin is the only drug that affects almost all factors in acne pathogenesis, but side-effects are common at the doses reported in published studies in the literature. The aim of this study was to investigate the efficacy of low daily dose isotretinoin in moderate to severe acne patients. The secondary objective was to measure the rate of relapse 5 years after the completion of therapy.Materials and Methods:In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…investigated the efficacy of low daily dose isotretinoin in moderate to severe acne patients. They found that low-dose isotretinoin was found to be a safe and effective choice for patients with moderate to severe scar prone acne vulgaris[ 17 ] so their results are consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…investigated the efficacy of low daily dose isotretinoin in moderate to severe acne patients. They found that low-dose isotretinoin was found to be a safe and effective choice for patients with moderate to severe scar prone acne vulgaris[ 17 ] so their results are consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Among these 3 groups, patients in group C have developed more side effects than other two groups. The side effects were cheilitis (100%), xerosis (38.10%), dryness of mouth and dry, rough hair (4.76%), dandruff (14.28%), erythema over face and hair loss (4.76%), elevated liver enzyme (9.52%) and elevated serum triglycerides (23.8%) which was similar to previous studies 3,10,[13][14][15][16] .…”
Section: Discussionsupporting
confidence: 88%
“…And in each tested formula amount of QRS was equal to that of ITT [1:1 ratio of ITT:QRS]. ( Table 4 ) [ 36 ].…”
Section: Resultsmentioning
confidence: 99%